Cost and Time Overrun of Public Infrastructure Project in The Philippines: Inhibiting Factors and Mitigating Measures - Layno, Jim Davis J.; Famadico, Jerome Jordan F. (Future Science / FSH-PH Publications, 2024)
Time and cost overruns in the implementation of infrastructure pro-jects are endless, as appears in all the implementing agencies of the government. According to the recent report of the state auditor, pro-jects were not completed within the specific contract time, while the socioeconomic planning body reported cost overruns on several big-ticket projects. This study proposes a frame of factors influencing overruns and mitigation actions as a contribution to the risk analy-sis of the implementation of projects as well as the project manage-ment initiative in monitoring and control of projects. By analyzing the datasets from Metro Manila, this study identified the most prevalent influencing factor of cost and time overruns faced in the implementation of infrastructure projects and developed measures to mitigate overruns. A total of 196 professionals responded to a questionnaire, and 12 participants were involved in unstructured interviews, which supported the data and results. To interpret and validate the data gathered, a relative importance index and a one-way analysis of variance test were used. The study revealed that the influencing factors leading to time overruns are inaccurate budget-ing, location of site, suspension of work, land acquisition, and varia-tion order, while for the cost overrun factors, inaccurate budgeting, variation order, inadequate project planning, market conditions, and inadequate site investigations prevail. A relationship between the perceptions of the 3 groups, namely the contractor, consultant, and implementing agency, with regards to the cost overrun factors was significant. However, with regards to the time overrun factors, they are not significant.